EZH2 promotes endometriosis progression through estrogen receptor and TNFα expression - Liu, Xiaohan; Cheng, Liqin; Huang, Liuxuan; Li, Mingyue; Shen, Qingjun; Li, Donghan; Dai, Kailing; Fu, Yanxia; Li, Min; Yao, Paul; Zeng, Liqin (Frontiers in Endocrinology, 2025)
Endometriosis is a chronic inflammatory gynecological condition marked by the presence of tissue similar to the endometrium grows outside the uterus, often leading pelvic pain and infertility. This study explores how enhancer of zeste homolog 2 (EZH2) influences endometriosis, particularly through its interaction with estrogen receptors (ERs). We found that EZH2 reduces ERα expression, allowing ERβ to bind to the tumor necrosis factor α (TNFα) promoter and increase TNFα levels, fueling inflammation. In mice, the EZH2 inhibitor GSK343 reduced TNFα levels and endometriosis progression, similar to gene knockdown of ERβ or EZH2. In human samples, endometriotic tissue showed higher levels of EZH2 and ERβ and lower levels of ERα than in controls. Thus, EZH2 promotes TNFα-driven inflammation, contributing to endometriosis. Targeting EZH2, as with GSK343, could be a promising therapeutic strategy for endometriosis treatment.